Seed structure and histochemistry in the palm Euterpe edulis - Panza, V. (2004)
The Euterpe edulis embryo consists of a prominent single cotyledon, a very short radicle-hypocotyl axis and an epicotyl. The epicotyl is obliquely angled with respect to the cotyledon; consequently it corresponds to one of the two categories recognized for palm seeds by DeMason (1988). Parenchyma, protoderm and procambium can be distinguished on the basis of position and shape of their cells, which are highly vacuolated with one central vacuole and the cytoplasm restricted to a thin parietal layer. Initial cells from both apical meristems are also vacuolated but they have small vacuoles distributed around the nuclei. Silica occurs in cell walls of some protodermal cells. Raphides, silica bodies and tannins all occur occasionally in vacuoles, especially in the basal cotyledon region. Most embryo cells lack storage reserves and exhibit an active state, with numerous mitochondria, RER cisternae and Golgi apparatus, indicating a strategy of continuous development without the interposition, at maturity, of a dry state. The endosperm consists of living cells with very large nuclei and thickened cell walls. Similar to the endosperm of other studied palm species, their cells exhibit a quiescent appearance with lipid, protein, minerals (in the cytoplasm) and mannans (in the cell walls) as the insoluble storage reserves. © 2004 The Linnean Society of London.